New Perspectives on Mimbres Archaeology : Three Millennia of Human Occupation in the North American Southwest - Roth, Barbara J. (University of Arizona Press, 2018)
Cover -- Title Page -- Copyright -- Contents -- Introduction: New Perspectives on Mimbres Archaeology / Roth, Gilman, and Anyon -- 1. First Farmers of the Mimbres Region / Turnbow, Roney, and Hard -- 2. Changing Perspectives on Pithouse Period Occupations in the Mimbres Region / Anyon and Roth -- 3. Making the Transition: Using New Data to Reassess the Mimbres Pithouse-to-Pueblo Period / Sedig, Lekson, and Roth -- 4. Mimbres Classic Period Architecture, Ceramics, and Religion: Maintaining Social Cohesion in the Face of Social Diversity / Gilman, Creel, and Gruber -- 5. Small Pueblo Sites of the Mimbres Classic Period: New Views and Interpretations / Stokes, Woods, and Toney -- 6. Mimbres Pottery: New Perspectives on Production and Distribution / Creel and Speakman -- 7. Mimbres Pottery Designs in Their Social Contexts / Hegmon, McGrath, O'Hara, and Russell -- 8. Variability in Mimbres Food and Food Procurement / Schollmeyer, Diehl, and Sandor -- 9. Continuity and Change in the Eastern Mimbres Area After A.D. 1130 / Schollmeyer, Nelson, and Hegmon -- 10. Continuity and Change in the Early Postclassic (A.D.1130 to 1300) in the Mimbres Valley / Putsavage and Taliaferro -- 11. Connectivity of Social Change in Mimbres and Points South / Nelson and Minnis -- 12. The Mimbres Foundation in the History of Nonprofit Archaeology / Doelle -- 13. Thoughts on Mimbres Archaeology / LeBlanc -- Contributors -- Index.